3D imaging system for the digitization of the Argentine museums collections - Morita, María Mercedes (2018)
3D images are increasingly used in the documentation of Cultural Heritage. The Laboratory of Laser Ablation of the Centro de Investigaciones Ópticas, Argentina, is carrying out a 3D digitization project of the collections of the museums of the Province of Buenos Aires, by using digital photogrammetry. A system called Mu3D was developed, that uses free software for Structure from Motion and 3D image processing. A combination of three software systems has been chosen in order to achieve a 3D model with the same accuracy of the results obtained by laser scanning techniques. The system, including a protocol for image acquisition, is being transferred to the museums for free, by training their staff and providing them assistance for the development of digitization programs and conservation actions.